The Effect of Fucoidan on Cellular Oxidative Stress and the CatD-Bax Signaling Axis in MN9D Cells Damaged by 1-Methyl-4-Phenypyridinium - Liang, Zhigang; Liu, Zhuli; Sun, Xuwen; Tao, Manli; Xiao, Xiao; Yu, Guoping; Wang, Xiaomin (Frontiers in Aging Neuroscience, 2019)
Background: The purpose of this study was to investigate the impact of fucoidan (FUC) on the oxidative stress response and lysosomal apoptotic pathways in the Parkinson disease (PD) cell model. Methods: The Dopaminergic nerve precursor cell line(MN9D) cells that served as a PD model in this study underwent damage induced by 100 μM 1-methyl-4-phenyl pyridine (MPP+). Cell viability was assessed after FUC treatment and intracellular SOD GSH was measured via immunofluorescence assay. Cellular changes in cathepsin D, Autophagy marker Light Chain 3-II (LC3-II), and apoptotic protein Bax were assessed by Western blot. The expression of Cat D, LC3-II, and B cell lymphoma-2-associated x protein (Bax) was also measured after addition of the cathepsin inhibitor, pepstatin A. Results: The results indicated that MN9D cell viability decreased by 50% within 24 h after 100 μM MPP+ induced toxicity. Pretreatment with 100 μM Fucoidan reduced cellular expression of LC3-II and CatD in 3 h and suppressed the induction of Bax protein. After pepstatin A treatment, Bax expression was significantly downregulated.FUC reversed the reduction of superoxide dismutase (SOD) L-Glutathione(GSH), decreased cell viability, and apoptosis induced by MPP+ in 6 h, suggesting that Fucoidan can attenuate damage to MN9D cells induced by MPP+. Conclusions: Fucoidan protected lysosomes, reduced the expression of LC3-II, inhibited the expression of CatD-Bax and the oxidative stress response, suppressed apoptosis, and thus conferred protective effects for dopaminergic neural cells. FUC may have neuroprotective effects on PD and further research is needed.